Current status on patient safety culture of medical staff at Xanh Pon Hospital in 2020 (Vietnam Journal of Community Medicine, 2021)
Background: Patient safety (ATNB) is to minimize possible medical incidents, thereby reducing the risk of harm to the patient during treatment and care at health facilities. Establishing a culture of patient safety is a top priority in improving the professional environment and improving the quality of treatment.Objective: Describe the status of patient safety culture of medical staff at the general hospitalSubjects and method: Cross-sectional study on 638 medical staff (HCWs) working at Xanh Pon Hospital, having worked at the hospital from 6 months or more, as of June 2020.Results: More than three-quarters of health workers gave positive reviews about the existing VHWs of Green Po General Hospital, of which two groups of criteria with the lowest positive response rate were Faculty / Division Staff (49.4%) and Behavior without accusation when there is error by the Faculty / Department (53.1%). The rate of positive assessment of each of the 12 aspects of the VHWs ranged from 57.0% to 92.6%.Conclusion: The hospital needs to improve the inappropriate procedures, increase the clarity and feasibility when applying it in practice.
Keywords: Patient safety culture, culture of safety, Xanh Pon